Integrating Mobile Technologies: Two Stage Study on Academic Performance and Social Presence - Ergun-Elverici, Sibel (MDPI, 2023)
The ubiquity of mobile technologies has sparked interest in their potential impact. However, current research predominantly concentrates on adults, neglecting the younger demographic that is more profoundly immersed in mobile technologies. To bridge this gap, this study introduces a specialized instructional design, integrating the widely used application Duolingo into English classes, to explore the ramifications of mobile technologies on the academic performance and social presence of high school students in their initial years. Conducted within a private school where English is mandatory, the research adopts a mixed-method approach, with quantitative and qualitative facets. Data collection comprises a needs analysis, a standardized English test (KET), a social presence scale and follow-up interviews. Participants were selected using purposive sampling, 16 students each for the experimental and control groups. Semi-structured interviews were conducted with eight voluntary participants. Analysis techniques, including t-tests for the social presence scale, descriptive analysis for interviews, and grading for exam results were applied. Noteworthy distinctions in students' academic performances were revealed through effect size measurements in writing (0.78), listening (1.01), and speaking (0.82), with a minor change in reading (-0.1). Additionally, a significant variation in social presence emerged (t = -9.194; p < 0.05). Qualitative themes emerged, highlighting Duolingo's entertainment value, curriculum alignment, content diversity, accessibility, parental consent, and teacher guidance. Quantitative results demonstrated Duolingo's positive impact on academic performance, while qualitative insights reflected students' enthusiasm for its integration. Findings invite a critical examination of the role of such technologies, prompting inquiries into their potential advantages and challenges.
Keywords: academic performance; Duolingo; educational technology; English as a foreign language (EFL); mobile technologies; social presence; technology integration; Web 2.0; COMMUNITY; CLASSROOM; CALL; Science & Technology - Other Topics; Environmental Sciences & Ecology